NILAI-NILAI LUHUR DALAM LELAGON DOLANAN (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2009)
Lelagon dolanan (children) contains a variety of high values of national culturewhich is useful for building character and identity of the nation. Dewasa inikondisi lelagon dolanan (anak) ibarat hidup segan mati tak mau. He wassurrounded by a variety of industrial art products that appear more glamorous,practical, and economical. To preserve, develop, and distribute it needs to supportfrom various parties both actors musical arts, government, media entrepreneurs,and society. Javanese gamelan music art perpetrators should be creative,innovative, creative, and productive working lelagon dolanan (children) whoactually follow the new development era. The government is expected to makepolicy, especially through formal education institutions in favor of thepreservation and development of lelagon dolanan. Employers can participate in themass media through the production and dissemination of copyrighted workspublicly lelagon dolanan. Thus, the public can access easily and cheaply lelagondolanan products (children).Kata kunci: lelagon dolanan, nilai, luhur, pelestarian, pengembangan